Dealer behavior in the specials market for US Treasury securities - Fleming, Michael J.; Garbade, Kenneth D. (Journal of Financial Intermediation, 2007)
We assess dealer behavior in the specials market for US Treasury securities by comparing dealer participation in the Federal Reserve's securities loan auctions with prices in the private market. Dealer behavior is generally consistent with the law of one price and apparent violations can largely be explained by institutional differences between the private market and the Fed's program. However, for auctions that are effectively noncompetitive, dealers regularly pass up true arbitrage opportunities and frequently overpay to borrow securities. Dealers apparently do not realize that certain auctions are noncompetitive, even though the information needed to discern this fact is publicly available in advance.